Management of Quality Improvement in Islamic Education Learning to Enter the Socio-Cultural Changes - Dadang Sahroni; Iim Wasliman; Daeng Arifin; Cahya Syaodih; Aeni Latifah (STAI Hubbulwathan Duri, 2022)
Social and cultural changes impact advances in Science and Technology (IPTEK) that occur at any time, especially in communication and information technology. As a result, these advances occurred in community activities in the fields of economy, law, politics, education, and others. This study aims to analyse how the management of improving the quality of Islamic Education (hereafter, PAI) learning in entering socio-cultural changes at two different state senior high schools in Sukabumi City, West Java. This article used a phenomenological study as the research design. Interviews and observations were conducted to collect the data. After that, the data was analysed using three stages, namely data reduction, data presentation, conclusion drawing and verification/interpretation. Based on the research focus on PAI learning management in entering socio-cultural changes in those two schools, the results of the research, in general, can be concluded that PAI teachers at those schools have understood and implemented PAI learning management in entering the socio-cultural change in accordance with applicable techniques and theories so that the learning process is conducive even though the results have not reached a very satisfactory target.